Exploring The Relationship Between Electronic Health Care Systems, Nursing Workload, And Quality Of Care; A Comprehensive Systematic Review (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Nursing workload and its impact on care quality and nurse wellbeing are critical concerns in healthcare settings. This study aimed to explore the relationship between electronic health systems, nursing workload, and quality of care through a review of relevant literature.Aim: The objective was to synthesize findings from selected studies to understand how electronic health systems influence nursing workload and subsequently affect the quality of patient care and nurse wellbeing.Method: A systematic review of literature conducted, focusing on studies that investigated the relationship between electronic health systems, nursing workload, and quality of care. Ten relevant studies were selected and analyzed for themes and sub-themes related to the research question.Results: The review identified several key themes, including the negative impact of high nursing workload on nurse wellbeing and patient care quality, the effectiveness of System Dynamics modeling in understanding workload impact, the association between workload and quality of care, and the perception of workload in nursing documentation practices.Conclusion: The findings underscore the critical importance of managing nursing workload effectively to enhance care quality and nurse wellbeing. System Dynamics modeling emerges as a valuable tool for understanding workload dynamics and identifying areas for intervention. Future research should focus on implementing targeted interventions to mitigate the negative effects of high workload on healthcare outcomes.